Not really a smoker? A study on the prevalence of and attitudes to occasional social smoking in a third level institution in Ireland - Hayes, Catherine (My University, 2021)
Background: Occasional smoking is defined as any smoking occurring on a less than daily basis. Social smoking, i.e. smoking primarily in social contexts, is a sub-group of occasional smoking. Data on occasional cigarette smoking and the subset of social smoking among third level students are limited. Objectives: (1) To determine prevalence of occasional/social smoking among third level students in an Irish university; (2) to evaluate students' attitudes to occasional/social smoking, including perceived benefits and harm; (3) to explore when students commenced occasional/social smoking, their reasons and continued smoking habits; and (4) to determine any influence of other factors, e.g. alcohol consumption, on occasional/social smoking. Methods: An anonymous online survey was distributed to undergraduates and postgraduates, using SurveyMonkey. Data were analysed in Microsoft Excel. Results: Of 18,407 students surveyed, 1310 (7.1%) responded;1267 (96.7%) provided adequate data for analysis. Of the 1267 students, 423 (33.4%) self-reported as current smokers of whom 106/1267 (8.4%) self-classified as daily smokers and 317/1267 (25%) as occasional smokers. The 25% of occasional smokers comprised 266/1267 (21%) social smokers and 51/1267 (4%) non-social smokers. Occasional smokers tended to start smoking earlier and think less about quitting than daily smokers. Of 423 current smokers, 386 (97.2%) reported that alcohol increased their smoking habits. Conclusion: Prevalence of self-reported occasional smoking among university students was higher than daily smoking. Most occasional smokers primarily smoked in social contexts. All current smokers reported that alcohol increased cigarette intake. Effective intervention campaigns tailored to determinants of occasional/social smoking are needed as part of induction to third level.
PUBLISHED
Keywords: Alcohol and smoking; Occasional smoking; Social smoking; Third level students